2012
DOI: 10.1007/s11033-012-2380-7
|View full text |Cite
|
Sign up to set email alerts
|

Association of endothelial nitric oxide synthase gene polymorphisms with classical risk factors in development of premature coronary artery disease

Abstract: Genetic polymorphism of the endothelial nitric oxide synthase (eNOS) affects the pathogenesis of atherosclerosis and associated with premature coronary artery disease (PCAD). We aimed to explore the association between Glu298Asp polymorphism of the eNOS gene and premature CAD in Egyptians, and the possible interaction between this polymorphism and other risk factors. The study population consisted of 116 patients with PCAD, and 119 controls. Glu298Asp polymorphism (rs1799983) of the eNOS gene was analyzed by p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
1
1

Citation Types

1
13
0

Year Published

2015
2015
2022
2022

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(15 citation statements)
references
References 36 publications
1
13
0
Order By: Relevance
“…This result could be associated with a low risk of developing HT in the participants of this study since variant alleles have been found to be responsible for an increased risk of HT [ 29 , 30 ]. Studies have shown that eNOS gene polymorphisms are associated with HT and some CVDs due to reduced production and/or bioavailability of NO [ 4 , 31 , 32 ]. However, Silva et al [ 3 ] emphasize that even if there is a deficiency in vasodilator production of NO due to a variant allele, the maintenance of good levels of TS may be beneficial to maintain normal BP levels.…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…This result could be associated with a low risk of developing HT in the participants of this study since variant alleles have been found to be responsible for an increased risk of HT [ 29 , 30 ]. Studies have shown that eNOS gene polymorphisms are associated with HT and some CVDs due to reduced production and/or bioavailability of NO [ 4 , 31 , 32 ]. However, Silva et al [ 3 ] emphasize that even if there is a deficiency in vasodilator production of NO due to a variant allele, the maintenance of good levels of TS may be beneficial to maintain normal BP levels.…”
Section: Discussionmentioning
confidence: 99%
“…Evidence supports the theory that several polymorphisms contribute to variations in the concentrations of some substances which influence blood pressure (BP) values. In this regard, the polymorphisms of endothelial nitric oxide synthase ( eNOS ) can influence nitric oxide (NO) formation, a powerful vasodilator with a critical role in BP control [ 3 , 4 ]. Since eNOS is related to an important pathway of cardiovascular control, the presence of variant allele polymorphisms in the gene that codes for eNOS could interfere directly in BP values [ 5 ].…”
Section: Introductionmentioning
confidence: 99%
“…Similarly, the role of the rs1799983 eNOS polymorphism has been demonstrated in the pathogenesis of cardiovascular diseases in adults [ 34 , 35 ], but has never been investigated in the pathogenesis of prematurity complications. We found that GT+TT rs1799983 eNOS genotypes increase the risk of BPD.…”
Section: Discussionmentioning
confidence: 99%
“…An increasing number of SNPs are being accepted as underlying contributors to numerous cardiovascular disorders. Different researchers have shown the importance of several polymorphisms in CCC susceptibility [ 21 , 28 , 33 , 46 , 47 ]. In vitro studies have suggested that the p.Asp298Glu polymorphism plays a functional role, with the Asp 298 variant being associated with a decreased eNOS activity [ 43 , 44 ], the consequences of which may include impaired collateral development.…”
Section: Discussionmentioning
confidence: 99%
“…CCL2 rs1024611 and rs1024610 have been associated with myocardial infarction [ 39 , 42 ]. NOS3 rs1799983 has functional consequences for the protein [ 43 , 44 ] which are associated with coronary arteriogenesis [ 45 , 46 ] and CAD [ 47 ]. ICAM1 rs5498 affects the primary structure of the protein and both it and rs3093030, located near the 3’ end of the gene, are related to sICAM1 plasma levels [ 48 51 ] and to coronary artery calcification [ 52 ].…”
Section: Methodsmentioning
confidence: 99%